THE ROLE OF AGRICULTURAL CREDIT IN THE GROWTH OF LIVESTOCK SECTOR: A CASE STUDY OF FAISALABAD - ABEDULLAH, N. MAHMOOD, M. KHALID1 AND S. KOUSER (Pakistan Veterinary Journal, 2009)
This study employed stratified random sampling approach to collect the input-output and socioeconomic data set to see the impact of credit on the growth of livestock sector in the rural areas. The income elasticities of meat and livestock products were highest compared to all other food items except fruits, defining the future role of livestock sector in our food basket. It was observed that credit availability expanded the livestock sector more than double (economies of size), which increased per family per month income from livestock sector by 181%. The elasticity values of family size, literacy rate (schooling years) and credit were 0.18, 0.05 and 0.06, respectively. The elasticity of family size was highest, followed by credit and literacy rate, indicating that adequate potential exists that can be explored to utilize unemployed and untrained rural labor in the agriculture sector. It would help to mitigate the increasing population pressure on mega cities of Pakistan by providing employment opportunities at the door steps of rural community.